Security/Mobility Politics of Movement - Leese, Matthias; Wittendorp, Stef (New Approaches to Conflict Analysis, 2017)
Mobility and security are key themes for students of international politics that assume a globalized world. This book brings together research that looks into the political regulation of movement with research that engages the material enablers of and constraints on such movement. The setup of the book explores overlaps between critical security studies and political geography in order to bridge the gap between disciplines that study aspects of global modernity and its politics and practices.The contributions to this book cover a broad range of topics that are bound together by their focus on both the politics and the material underpinnings of movement. The authors engage diverse themes such as internet infrastructure, the circulation of data, discourses of borders and bordering, bureaucracy, and citizenship, thereby identifying common themes of Security/Mobility today.